so my equation is x^{2}+y^{2}-4x+2y-4=0
i know the formula is (x-h)^{2}+(y-k)^{2}=r^{2}
x^{2}-4x+y^{2}+2y-4=0
the Y is (y-2)^{2} which makes my k equal to positive 2 just having trouble with the h and radius
so my equation is x^{2}+y^{2}-4x+2y-4=0
i know the formula is (x-h)^{2}+(y-k)^{2}=r^{2}
x^{2}-4x+y^{2}+2y-4=0
the Y is (y-2)^{2} which makes my k equal to positive 2 just having trouble with the h and radius
ok I understand that question but given this example here 5 x^2 - 10 x +5 y^2 - 8 y - 6 = 0 .
I worked it down to (x-1)^2 and (y-0.8)^2 =
I divided out 5 and was left with x^2-2x+y^2-1.6y-1.2=0
then its x^2-2x+1 + y^2-1.6y ?= 1.2-1 (?)